Transforming technical assistance for more effective health services delivery in Africa: the WHO multi-country assignment teams experience - Ba, Ndoungou Salla; Usman, Abdulmumini; Gasasira, Alex; Kabore, Patrick; Achu, Bei; Kulausa, Hyelni; Chanda, Emmanuel; Olu, Olushayo Oluseun; Cabore, Joseph; Moeti, Matshidiso (Frontiers in Public Health, 2025)
The importance of technical assistance in fast tracking countries’ progress to the attainment of global and regional public health goals cannot be overemphasized. In this regard, the World Health Organization Regional Office for Africa, piloted a new, innovative, and stepwise technical assistance delivery approach from 2022 called the Multi-Country Assignment Teams. Given the experimental nature of this approach, this case study assessed its effectiveness in enhancing the quality and timeliness of technical assistance in the region, as well as identifying and addressing any initial challenges. The progress of MCAT activities were assessed using secondary data sourced from the MCAT monitoring and evaluation database, along with travel data from WHO’s Global Management System (GSM) covering April 2022 to September 2023. The findings highlight the potential of the Multi-Country Assignment Teams as a promising solution for providing quality and timely technical assistance to African countries. Most (67%) of the 928 technical support activities planned between April 2022 to December 2023 were successfully implemented. In general, most Multi-Country Assignment Teams host countries received more support than non-host countries except for Mozambique, Zimbabwe, and Kenya Multi-Country Assignment Teams where the technical support was greater in non-host countries. Data on the Multi-Country Assignment Teams duty travels revealed that there was a total of 185 missions in 2022. Out of this, 65 (35%) were within the Multi-Country Assignment Teams’ host country, 27 (15%) were in non-host countries, and 93 (50%) were not Multi-Country Assignment Team-related. Despite these achievements, several challenges that hinder the model’s accelerated implementation persist. These include delays in implementing the approach’s activities due to delayed recruitment of staff and inadequate funding and maldistribution of the approach’s activities between host and non-host countries. Additionally, many of the approach’s activities were non-related to its core function which hampered the effective and timely delivery of their support. Moving forward, it is crucial to build on the successes so far achieved by Multi-Country Assignment Teams while addressing the challenging issues, particularly by improving awareness of their functions and ensuring adequate staffing and funding.